Robotics in the Resocialization of Youngsters and Teenagers in Socio-Educational Measures - Pancieri, Jussara; Siqueira, Fábio; Oliveira, Márcia; Santos, Marcelo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This paper presents a proposal and an experience report of an educational robotics course integrated to the process of resocialization of youngsters and teenagers in socio-educational measures. This proposal adopts a teaching approach oriented to the development of comprehension, analysis, logical reasoning, creativity and collaboration skills in order to develop in these young people real world problemsolving skills. The main challenge of this proposal is to favor the assimilation of the contents and the development of robotics practice outside the classroom, since, in accommodation, no course material is accessible from paper and pencil to robotics practice instruments. Thus, the main differential of this work is literally working the computational thinking in spaces of deprivation of liberty in order to develop ideas for problem solving tasks. The results of this developed experience point to excellent opportunities for resocialization and professional orientation of young people in socio-educational measures through the teaching of robotics.